Legacy Effects of Plant Community Structure Are Manifested in Microbial Biofilm Development With Consequences for Ecosystem CO 2 Emissions - Kevin H. Wyatt; Jillian Cieslik; Catherine M. Dieleman; Evan S. Kane; Allison R. Rober; Barrett Sullivan; Merritt R. Turetsky (Global Change Biology, 2024)
To better understand linkages between hydrology and ecosystem carbon flux in northern aquatic ecosystems, we evaluated the relationship between plant communities, biofilm development, and carbon dioxide (CO 2 ) exchange following long‐term changes in hydrology in an Alaskan fen. We quantified seasonal variation in biofilm composition and CO 2 exchange in response to lowered and raised water table position (relative to a control) during years with varying levels of background dissolved organic carbon (DOC). We then used nutrient‐diffusing substrates (NDS) to evaluate cause–effect relationships between changes in plant subsidies (i.e., leachates) and biofilm composition among water table treatments. We found that background DOC concentration determined whether plant subsidies promoted net autotrophy or heterotrophy on NDS. In conditions where background DOC was ≤ 40 mg L −1 , plant subsidies promoted an autotrophic biofilm. Conversely, when background DOC concentration was ≥ 50 mg L −1 , plant subsidies promoted heterotrophy. Greater light attenuation associated with elevated levels of DOC may have overwhelmed the stimulatory effect of nutrients on autotrophic microbes by constraining photosynthesis while simultaneously allowing heterotrophs to outcompete autotrophs for available nutrients. At the ecosystem level, conditions that favored an autotrophic biofilm resulted in net CO 2 uptake among all water table treatments, whereas the site was a net source of CO 2 to the atmosphere in conditions that supported greater heterotrophy. Taken together, these findings show that hydrologic history interacts with changes in dominant plant functional groups to alter biofilm composition, which has consequences for ecosystem CO 2 exchange.